Daily Report -no. 2 TGWU, 6 May 1926 (page 1)
1926-05-06 "Daily Report -no. 2 TGWU, 6 May 1926 (page 1)" [g0591001.jpg], 6 May 1926, Transport and General Workers' Union Union Reports and Correspondence